Composite nanodot loaded porous carbon nitride photocatalyst as well as preparation method and application thereof

Porous carbon nitride was prepared by using a mixed precursor of melamine, cyanuric acid and trithiocyanate, and CoO and Ni nanodots were loaded in air and Ar-H2 atmospheres. This solved the problem of low photocatalytic efficiency of graphitic carbon nitride photocatalysts and achieved high-efficiency visible light photocatalytic hydrogen production performance.

CN120815566APending Publication Date: 2025-10-21SHAANXI DOUBLE CARBON ZHIHUI TECHNOLOGY DEVELOPMENT CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511078376.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing graphite carbon nitride (g-C3N4) photocatalysts have low photocatalytic hydrogen production efficiency due to their small specific surface area, narrow visible light absorption range, low electrical conductivity, and high recombination rate of photogenerated electrons and holes.

Method used

Porous carbon nitride was prepared by using a mixed precursor of melamine, cyanuric acid and thiocyanic acid, and CoO and Ni nanodots were loaded under air and Ar-H2 atmospheres, respectively, to form a uniformly distributed porous carbon nitride photocatalyst loaded with composite nanodots.

Benefits of technology

It significantly improves the photocatalytic hydrogen production performance, with a hydrogen production activity of 1780 μmol h⁻¹ g⁻¹. It is low in cost, has a wide range of applications, and the preparation process is simple.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120815566A_ABST
    Figure CN120815566A_ABST
Patent Text Reader

Abstract

The invention relates to a composite nanodot loaded porous carbon nitride photocatalyst as well as a preparation method and application thereof, and the preparation method comprises the following steps: calcining a precursor formed by mixing melamine, cyanuric acid and trithiocyanuric acid to obtain porous carbon nitride, and loading cobalt oxide nanodots and nickel nanodots on the porous carbon nitride in two steps, the composite nanodot loaded porous carbon nitride photocatalyst with excellent visible light catalytic hydrogen production performance is obtained; when the composite nanodot loaded porous carbon nitride photocatalyst obtained by the method is used for photocatalytic hydrogen production, an activity test result shows that the activity of the photocatalyst prepared by the method is improved by 222.5 times compared with that before modification; the preparation method disclosed by the invention has the advantages of high reaction efficiency and good performance of the obtained photocatalyst, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic hydrogen production, and specifically relates to a composite nano-dot loaded porous carbon nitride photocatalyst, a preparation method and an application thereof. Background Art

[0002] Graphitic carbon nitride (g-C3N4) has broad application prospects in visible light photocatalysis due to its unique energy band structure, stable physicochemical properties, and readily available, non-toxic raw materials. However, due to its small specific surface area, narrow visible light absorption range, low electrical conductivity, high recombination rate of photogenerated electrons and holes, and few surface reactive sites, the photocatalytic performance of pristine g-C3N4 is significantly limited, resulting in low photocatalytic hydrogen production efficiency. Therefore, targeted modification of pristine g-C3N4 to improve its photocatalytic hydrogen production efficiency is highly necessary.

[0003] Among the many catalyst modification methods, loading metal nanodots onto the surface of g-C3N4 is a highly effective approach. Porous carbon nitride, prepared by calcining a precursor obtained from a mixture of melamine, cyanuric acid, and thiocyanuric acid, exhibits a significantly higher surface area than pristine g-C3N4, providing more attachment sites for the metal nanodots. All three raw materials are readily available and readily available, and calcination is performed in a tubular furnace, resulting in a simple, time-saving preparation process and easily achievable reaction conditions.

[0004] In the process of loading nanodots on the porous carbon nitride surface, anhydrous ethanol is used as a solvent, and then rotary evaporation is used for solid-liquid separation to achieve the composite of metal ions and porous carbon nitride. Anhydrous ethanol has the characteristics of being volatile, which ensures that the solid-liquid separation is carried out quickly and efficiently. The stable operation of the rotary evaporation process ensures that the metal ions are evenly loaded on the porous carbon nitride surface. Subsequent calcination in air and Ar-H2 gas atmospheres ensures the formation of CoO and Ni nanodots, respectively. The entire preparation process ensures that the two nanodots are evenly distributed on the porous carbon nitride surface.

[0005] The Chinese Journal of Catalysis 43(2022)536–545 reported that ultrathin carbon nitride nanosheets were prepared by calcining dicyandiamide and ammonium chloride as precursors. These nanosheets were then dispersed in a Ni(CH3COO)2 water-methanol solution and subjected to in situ photoreduction deposition of monodisperse Ni clusters under illumination to obtain Ni cluster-anchored carbon nitride. The ACS Nano 2023,17,11869–11881 published that Ag1-CN, embedded with single Ag atoms, was prepared by calcining melamine-cyanuric acid supramolecules under nitrogen. This was then solvent-thermally treated in N-methylpyrrolidone with CoCl2 and NaH2PO2 to obtain P-doped carbon nitride with Co-Ag diatomic sites co-loaded with Ag nanoparticles. According to Mater. Chem. Front., 2022, 6, 3706–3715, methyl cellulose and sodium chloride were dissolved in water, sodium lignin sulfonate and cobalt acetate were added, and the mixture was spray-dried to obtain a precursor. The precursor was nitrogen pre-carbonized, washed to remove NaCl, and then calcined to obtain hollow CoO X Embedded nitrogen-doped three-dimensional porous carbon catalysts. The synthesis methods reported in the above articles for modifying carbon nitride by supporting metal or metal oxide nanoparticles as co-catalysts have obvious shortcomings: 1. The synthesis process is cumbersome and complex, and the separation of the solvent and the catalyst requires multiple drying steps, which is time-consuming; 2. The large amount of added metal ions makes the metal or metal oxide clusters produced by calcination prone to aggregation, affecting catalytic efficiency, while also failing to fully utilize the catalytic performance of the co-catalyst, resulting in unnecessary losses. In particular, the use of precious metals further increases costs.

[0006] "Nature Communications, 2021, 12: 3181" announced: Mesoporous graphite phase carbon nitride and ethylenediamine iodide platinum (II) dimer dinitrate were dissolved in N, N-dimethylformamide, stirred and centrifuged, and the precipitate was washed with N, N-dimethylformamide / methanol and calcined in a nitrogen atmosphere to obtain diatomic Pt loaded on mesoporous graphite phase carbon nitride. The modified carbon nitride method mentioned in this article can make full use of the significant contribution of Pt single atoms to photocatalytic performance, thereby significantly improving the photocatalytic performance of the photocatalyst. However, the entire reaction process is very cumbersome. In addition, the N, N-dimethylformamide used has certain toxicity, which increases the risk of synthesis. At the same time, the Pt used is a precious metal, which will significantly increase the cost of synthesis. Summary of the Invention

[0007] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a porous carbon nitride photocatalyst loaded with composite nanodots, and a preparation method and application thereof; porous carbon nitride is obtained by calcining a precursor mixed with melamine, cyanuric acid and thiocyanic acid, and then the porous carbon nitride is loaded with CoO nanodots and Ni nanodots in two steps to obtain a porous carbon nitride photocatalyst loaded with composite nanodots with excellent visible light catalytic hydrogen production performance. The preparation process is simple and the reaction conditions are easy to achieve, the cost is low, and the application scenarios are wide.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a composite nanodot-loaded porous carbon nitride photocatalyst comprises the following steps:

[0010] Step 1, weighing melamine, cyanuric acid and thiocyanic acid in a mass ratio of (1.3-1.36):1.26:1;

[0011] Step 2: At room temperature, the melamine and cyanuric acid weighed in step 1 are added successively to 100-140 mL of deionized water, and stirred to obtain a mixed solution of melamine and cyanuric acid; the weighed thiocyanuric acid is added to 100-140 mL of deionized water to dissolve to obtain a thiocyanuric acid solution;

[0012] Step 3, adding the mixed solution of melamine and cyanuric acid obtained in step 2 dropwise to the thiocyanuric acid solution, stirring for 9-11 hours, filtering and drying to obtain a solid supramolecular polymer, placing the obtained solid supramolecular polymer in a vacuum oven at 50-70° C. and drying for 9-11 hours, grinding into powder to obtain a carbon nitride precursor;

[0013] Step 4: The carbon nitride precursor obtained in step 3 is heated at 2-4 ° C min in N2 atmosphere. -1 The heating rate is increased to 550-650°C and maintained for 1-3 hours, and then the temperature is naturally lowered to obtain porous carbon nitride;

[0014] Step 5: Dissolve the porous carbon nitride obtained in step 4 in anhydrous ethanol, ultrasonicate for 10-15 min, then add the CoCl2 ethanol solution dropwise to the solution and stir for 4-6 h, then perform rotary evaporation to obtain powder, and heat the powder at 2.5-3.5 ° C min -1 The heating rate was increased to 180-220° C. and kept at this temperature for 1.5-2.5 hours, and then naturally cooled to obtain a porous carbon nitride photocatalyst loaded with CoO nanodots;

[0015] Step 6: dissolve the CoO nanodot-loaded porous carbon nitride photocatalyst obtained in step 5 in anhydrous ethanol, ultrasonicate for 10-15 min, add Ni(NO3)2 anhydrous ethanol solution dropwise, stir for 4-6 h, and then rotary evaporate again to obtain powder; the obtained powder is heated at 2.5-3.5℃min in an Ar-H2 atmosphere. -1 The heating rate is increased to 180-220° C. and kept warm for 1.5-2.5 hours to obtain a loaded composite nano-dot porous carbon nitride photocatalyst for photocatalytic hydrogen production.

[0016] In step 4, the temperature is raised by calcination, and N2 gas is first introduced before calcination, and the temperature is maintained at room temperature for 20-40 minutes.

[0017] In step 5, 60-100 mg of the porous carbon nitride obtained in step 4 is dissolved in 40-60 mL of anhydrous ethanol.

[0018] Add CoCl2 ethanol solution in step 5 2+ The mass ratio of the porous carbon nitride is 0.25-1 wt %.

[0019] In step 6, the obtained CoO nanodot-loaded porous carbon nitride photocatalyst is dissolved in 40-60 mL of anhydrous ethanol.

[0020] Add Ni(NO3)2 anhydrous ethanol solution as described in step 6, Ni 2+ The mass ratio of the porous carbon nitride photocatalyst to the cobalt oxide nanodots is 0.5-1.5 wt %.

[0021] A loaded composite nano-dot porous carbon nitride photocatalyst prepared according to the method.

[0022] A composite nano-dot loaded porous carbon nitride photocatalyst prepared according to the method is used in photocatalytic hydrogen production.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention uses porous carbon nitride fired from a self-assembled precursor of melamine, cyanuric acid, and thiocyanuric acid. Compared with other conventional carbon nitrides fired with urea or melamine, the use of thiocyanuric acid introduces the S element into the precursor. Under calcination conditions of 600°C, the formed porous carbon nitride has a significantly improved specific surface area and forms more pores, which not only provides more attachment sites for subsequent metal nanodots, but also is more conducive to the carrier transport of the photocatalytic reaction, thereby improving the performance of the photocatalytic hydrogen production reaction.

[0025] 2. The present invention loads two kinds of nanodots on the surface of porous carbon nitride in two steps. First, CoO nanodots are synthesized in an air atmosphere, and then Ni nanodots are synthesized in an Ar-H2 atmosphere. The reaction conditions of 200°C will not reduce the CoO nanodots while achieving the formation of Ni nanodots. The surface of the prepared porous carbon nitride photocatalyst loaded with composite nanodots for photocatalytic hydrogen production is evenly loaded with two different nanodots, effectively improving the visible light catalytic hydrogen production performance.

[0026] 3. The photocatalytic hydrogen production test showed that the visible light photocatalytic hydrogen production activity of the composite nanodot porous carbon nitride photocatalyst prepared by the present invention was 1780 μmol h -1 g -1 , which is 222.5 times that of porous carbon nitride photocatalyst.

[0027] 4. Since the present invention uses ethanol as a solvent, no other impurities remain after rotary evaporation, and no other substances are generated after calcination in an Ar-H2 atmosphere in a tubular furnace, so that the product does not need further washing process.

[0028] 5. The raw materials used in the present invention are cheap and abundant, and at the same time do not carry precious metals. It is green, environmentally friendly and non-toxic, and has wide promotion and application value.

[0029] In summary, the catalyst of the present invention has excellent visible light catalytic hydrogen production performance, a simple preparation process, easy-to-achieve reaction conditions, low cost, and a wide range of application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the preparation method of composite nanodot-loaded porous carbon nitride photocatalyst for photocatalytic hydrogen production.

[0031] Figure 2 This is a bar graph of the visible light hydrogen production rate of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, 3, 4, 5, 6, and 7.

[0032] Figure 3 This is a diagram showing the hydrogen production stability of the loaded composite nanodot porous carbon nitride photocatalyst synthesized in Example 1.

[0033] Figure 4 This is a bar graph of the visible light hydrogen production rate of the loaded composite nanodot porous carbon nitride photocatalyst synthesized in Examples 1, 2, 3, 4, 5, 6, 7, 8, and 9.

[0034] Figure 5 1 and 2 are X-ray diffraction patterns of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3.

[0035] Figure 6The scanning electron microscope images of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Example 1 are shown in FIG. Figure 6 (a) is a scanning electron microscope image of the composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1. Figure 6 (b) is a scanning electron microscope image of the porous carbon nitride synthesized in Comparative Example 1.

[0036] Figure 7 This is a transmission electron microscope image of the composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1.

[0037] Figure 8 This is the in-situ X-ray photoelectron spectrum of the porous carbon nitride photocatalyst synthesized in Example 1, where Figure 8 (a) is the XPS C 1s spectrum of the composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1. Figure 8 (b) is the XPS N1s spectrum of the composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1, Figure 8 (c) is the XPS Ni 2p spectrum of the composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1, Figure 8 (d) is the XPS Co 2p spectrum of the composite nanodot-loaded porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1.

[0038] Figure 9 The UV-visible absorption spectra of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown.

[0039] Figure 10 The electron paramagnetic resonance spectra of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown.

[0040] Figure 11 Steady-state fluorescence spectra of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described in detail below with reference to the accompanying drawings and embodiments. The content of the present invention is specifically described below with reference to the embodiments. The following description is not intended to limit the present invention.

[0042] A series of porous carbon nitride photocatalysts for photocatalytic hydrogen production prepared according to the method of the present invention are specifically as follows.

[0043] Example 1

[0044] This embodiment provides a method for preparing a composite nanodot-loaded porous carbon nitride photocatalyst, comprising:

[0045] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0046] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0047] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0048] Step 4: 1 g of carbon nitride precursor powder was placed in a porcelain boat, heated to 600°C at 3°C / min in a tube furnace in a N2 atmosphere, maintained for 2 h, and then naturally cooled to room temperature to obtain porous carbon nitride (PCN).

[0049] Step 5: Take 80 mg of the porous carbon nitride PCN described in step 4 and dissolve it in 60 mL of anhydrous ethanol. After ultrasonic treatment for 15 min, add CoCl2 ethanol dropwise (Co in the CoCl2 ethanol solution) 2+ The mass ratio of the porous carbon nitride to the mass ratio of 0.5wt%) was stirred for 5h, and then the powder was placed in a muffle furnace and heated at 3℃min -1 The heating rate was raised to 200 °C and maintained for 2 h. After cooling naturally, the porous carbon nitride photocatalyst PCN-CoO loaded with CoO nanodots was obtained. 0.5 ;

[0050] Step 6: Take the PCN-CoO obtained in step 5 0.5 After being dissolved in 60 mL of anhydrous ethanol and ultrasonically treated for 15 min, 1 wt% Ni(NO3)2 anhydrous ethanol solution was added dropwise thereto, stirred for 5 h and then rotary evaporated again. The obtained powder was then placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was raised to 200 ° C and maintained for 2 h. After cooling naturally, the composite nano-dot porous carbon nitride photocatalyst Ni1-PCN-CoO for photocatalytic hydrogen production was obtained. 0.5 .

[0051] Example 2

[0052] A method for preparing a composite nanodot-loaded porous carbon nitride photocatalyst comprises the following steps:

[0053] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0054] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0055] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0056] Step 4: 1 g of carbon nitride precursor powder was placed in a porcelain boat, heated to 600°C at 3°C / min in a tube furnace in a N2 atmosphere, maintained for 2 h, and then naturally cooled to room temperature to obtain porous carbon nitride (PCN).

[0057] Step 5: 80 mg of the porous carbon nitride PCN described in step 4 was dissolved in 60 mL of anhydrous ethanol. After ultrasonic treatment for 15 min, CoCl2 ethanol solution was added dropwise to the solution (Co in the CoCl2 ethanol solution was added). 2+ The mass ratio of the porous carbon nitride to the mass ratio of the porous carbon nitride was 0.25 wt%) and stirred for 5 h, and then subjected to rotary evaporation. The obtained powder was placed in a muffle furnace and heated at 3 ° C min -1 The heating rate was raised to 200 °C and maintained for 2 h. After cooling naturally, the porous carbon nitride photocatalyst PCN-CoO loaded with CoO nanodots was obtained. 0.25 ;

[0058] Step 6: Take the PCN-CoO obtained in step 5 0.5 After being dissolved in 60 mL of anhydrous ethanol and ultrasonically treated for 15 min, 1 wt% Ni(NO3)2 anhydrous ethanol solution was added dropwise, stirred for 5 h, and then rotary evaporated again. The obtained powder was placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was raised to 200 ° C and maintained for 2 h. After cooling naturally, the composite nano-dot porous carbon nitride photocatalyst Ni1-PCN-CoO for photocatalytic hydrogen production was obtained. 0.25 .

[0059] Example 3

[0060] A method for preparing a composite nanodot-loaded porous carbon nitride photocatalyst comprises the following steps:

[0061] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0062] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0063] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0064] Step 4: 1 g of carbon nitride precursor powder was placed in a porcelain boat, heated to 600°C at 3°C / min in a tube furnace in a N2 atmosphere, maintained for 2 h, and then naturally cooled to room temperature to obtain porous carbon nitride (PCN).

[0065] Step 5: 80 mg of the porous carbon nitride PCN described in step 4 was dissolved in 60 mL of anhydrous ethanol. After ultrasonic treatment for 15 min, CoCl2 ethanol solution was added dropwise to the solution (Co in the CoCl2 ethanol solution was added). 2+ The mass ratio of the porous carbon nitride was 1 wt %) and stirred for 5 h, and then subjected to rotary evaporation. The obtained powder was placed in a muffle furnace and heated at 3 ° C min -1 The heating rate was increased to 200 °C and maintained for 2 h, and then naturally cooled to obtain the CoO nanodot-loaded porous carbon nitride photocatalyst PCN-CoO1;

[0066] Step 6: Take the PCN-CoO obtained in step 5 0.5 After being dissolved in 60 mL of anhydrous ethanol and ultrasonically treated for 15 min, 1 wt% Ni(NO3)2 anhydrous ethanol solution was added dropwise, stirred for 5 h, and then rotary evaporated again. The obtained powder was placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was increased to 200°C and maintained for 2 hours, and after natural cooling, a composite nano-dot porous carbon nitride photocatalyst Ni1-PCN-CoO1 loaded for photocatalytic hydrogen production was obtained.

[0067] Example 4

[0068] The preparation process of this embodiment is the same as that of embodiment 1, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 0.5wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 0.5 -PCN-CoO 0.5 .

[0069] Example 5

[0070] The preparation process of this embodiment is the same as that of embodiment 1, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 1.5 wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 1.5 -PCN-CoO 0.5 .

[0071] Example 6

[0072] The preparation process of this embodiment is the same as that of embodiment 2, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 0.5wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 0.5 -PCN-CoO 0.25 .

[0073] Example 7

[0074] The preparation process of this embodiment is the same as that of embodiment 2, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 1.5 wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 1.5 -PCN-CoO 0.25 .

[0075] Example 8

[0076] The preparation process of this embodiment is the same as that of embodiment 3, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 0.5wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 0.5 -PCN-CoO1.

[0077] Example 9

[0078] The preparation process of this embodiment is the same as that of embodiment 3, except that the mass fraction of the added Ni(NO3)2 anhydrous ethanol solution is 1.5 wt%, and the composite nano-dot porous carbon nitride photocatalyst Ni for photocatalytic hydrogen production is obtained. 1.5 -PCN-CoO1.

[0079] Comparative Example 1

[0080] Porous carbon nitride photocatalyst

[0081] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0082] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0083] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0084] Step 4: Take 1 g of carbon nitride precursor powder and place it in a porcelain boat. In a tube furnace in a N2 atmosphere, heat it to 600°C at 3°C / min, maintain it for 2 hours, and then cool it naturally to room temperature to obtain porous carbon nitride PCN.

[0085] Comparative Example 2

[0086] Single nanodot porous carbon nitride photocatalyst Single nanodot porous carbon nitride photocatalyst

[0087] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0088] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0089] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0090] Step 4: 1 g of carbon nitride precursor powder was placed in a porcelain boat, heated to 600°C at 3°C / min in a tube furnace in a N2 atmosphere, maintained for 2 h, and then naturally cooled to room temperature to obtain porous carbon nitride (PCN).

[0091] Step 5: 80 mg of the porous carbon nitride PCN described in step 4 was dissolved in 60 mL of anhydrous ethanol. After ultrasonic treatment for 15 min, 0.5 wt% CoCl2 ethanol solution was added dropwise to the solution and stirred for 5 h. The resulting powder was then rotary evaporated and placed in a muffle furnace at 3 °C min -1 The heating rate was raised to 200 °C and maintained for 2 h. After cooling naturally, the porous carbon nitride photocatalyst PCN-CoO loaded with CoO nanodots was obtained. 0.5 ;

[0092] Comparative Example 3

[0093] Single nanodot-loaded porous carbon nitride photocatalyst

[0094] Step 1: Weigh 1.33 g of melamine, 1.26 g of cyanuric acid, and 1 g of thiocyanic acid;

[0095] Step 2: 1.33 g of melamine and 1.26 g of cyanuric acid were dissolved in 120 mL of deionized water and stirred for 10 min to obtain a mixed solution of melamine and cyanuric acid; 1 g of thiocyanic acid was dissolved in 120 mL of deionized water and stirred for 10 min;

[0096] Step 3: adding the mixed solution of melamine and cyanuric acid dropwise to the thiocyanuric acid solution and stirring for 10 hours; filtering the resulting solution to obtain a light yellow solid, drying the solid in a vacuum oven at 60° C. and grinding it into a powder to obtain a carbon nitride precursor;

[0097] Step 4: 1 g of carbon nitride precursor powder was placed in a porcelain boat, heated to 600°C at 3°C / min in a tube furnace in a N2 atmosphere, maintained for 2 h, and then naturally cooled to room temperature to obtain porous carbon nitride (PCN).

[0098] Step 5: 80 mg of the porous carbon nitride PCN described in step 4 was dissolved in 60 mL of anhydrous ethanol and ultrasonically treated for 15 min. 1 wt% Ni(NO3)2 anhydrous ethanol solution was added dropwise thereto. After stirring for 5 h, the mixture was rotary evaporated again. The obtained powder was placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was increased to 200° C. and maintained for 2 h, and then naturally cooled to obtain Ni1-PCN loaded composite nanodot porous carbon nitride photocatalyst for photocatalytic hydrogen production.

[0099] Comparative Example 4

[0100] Porous carbon nitride photocatalyst

[0101] 80 mg of porous carbon nitride (PCN) was dissolved in 60 mL of anhydrous ethanol solution and ultrasonically treated for 15 min. 0.5 wt% CoCl2 anhydrous ethanol solution and 1 wt% Ni(NO)3 anhydrous ethanol solution were added dropwise, stirred for 5 h, and then rotary evaporated. The resulting powder was placed in a tube furnace and heated to 200 ° C at a rate of 3 ° C min-1 under Ar-H2 atmosphere and maintained for 2 h. The control example 4 was obtained by natural cooling, which was recorded as Ni1Co 0.5 -PCN.

[0102] Comparative Example 5

[0103] Porous carbon nitride photocatalyst

[0104] 80 mg of porous carbon nitride (PCN) was dissolved in 60 mL of anhydrous ethanol solution, ultrasonicated for 15 min, stirred for 5 h, and then rotary evaporated. The resulting powder was placed in a muffle furnace and heated at 3 °C min -1The heating rate was raised to 200 °C and maintained for 2 h. After cooling naturally, the mixture was dissolved in 60 mL of anhydrous ethanol solution again. After ultrasonic treatment for 15 min, the mixture was stirred for 5 h and then rotary evaporated again. The obtained powder was placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was increased to 200°C and maintained for 2 h, and then naturally cooled to obtain Control Example 5, which was recorded as Ni0-PCN-CoO0.

[0105] Comparative Example 6

[0106] Single nanodot-loaded porous carbon nitride photocatalyst

[0107] 80 mg of CoO nanodot-loaded porous carbon nitride photocatalyst 0.5Co-PCN was dissolved in 60 mL of anhydrous ethanol and ultrasonically treated for 15 min. After stirring for 5 h, it was rotary evaporated again. The obtained powder was placed in a tube furnace and heated at 3 °C min under an Ar-H2 atmosphere. -1 The heating rate was raised to 200 ° C and maintained for 2 h. After cooling naturally, the control example 6 was obtained, which was recorded as Ni0-PCN-CoO 0.5 .

[0108] Comparative Example 7

[0109] Single nanodot-loaded porous carbon nitride photocatalyst

[0110] 80 mg of porous carbon nitride (PCN) was dissolved in 60 mL of anhydrous ethanol solution, ultrasonicated for 15 min, stirred for 5 h, and then rotary evaporated. The resulting powder was placed in a muffle furnace and heated at 3 °C min -1 The heating rate was raised to 200 ° C and maintained for 2 h. After cooling naturally, it was dissolved in 60 mL of anhydrous ethanol solution again. After ultrasonic treatment for 15 min, Ni (NO3) 2 anhydrous ethanol solution was added dropwise. After stirring for 5 h, the rotary evaporation was performed again. The obtained powder was placed in a tube furnace and heated at 3 ° C min under Ar-H2 atmosphere. -1 The heating rate was increased to 200° C. and maintained for 2 h. After natural cooling, Control Example 7 was obtained, which was recorded as Ni1-PCN-CoO0.

[0111] Performance evaluation:

[0112] Figure 1 This is a schematic diagram of the preparation method of the composite nano-dot-loaded porous carbon nitride photocatalyst for photocatalytic hydrogen production. The synthesis process of the embodiment photocatalysts in the present invention is shown in the figure.

[0113] Figure 2The following is a bar graph showing the visible light hydrogen production rate of the porous carbon nitride photocatalyst synthesized in Example 1 and Comparative Examples 1 to 7. The photocatalytic hydrogen production test method is as follows: 20 mg of the photocatalyst is dispersed in 70 mL of a 10% triethanolamine aqueous solution, and argon is purged through the reactor for 20 minutes before illumination to remove oxygen from the system. The magnetic stirrer is then turned on, and the xenon lamp is powered on. The activity of the synthesized porous carbon nitride in photocatalytic hydrogen production is evaluated by detecting the amount of hydrogen produced in the photocatalytic system. Figure 2 As can be seen, the photocatalytic hydrogen production activity of the porous carbon nitride loaded with composite nanodots is higher than that of the photocatalysts in the other examples and the control example, indicating that the method of modifying graphite-phase carbon nitride by loading composite nanodots is an effective means of improving the photocatalytic performance of graphite-phase carbon nitride photocatalysts. The significantly improved photocatalytic hydrogen production activity of Example 1 compared to Control Examples 1-7 indicates that the interaction between the two uniformly loaded nanodots in Example 1 is the main factor in improving the photocatalytic hydrogen production activity, while the effects of the rotary evaporation and calcination treatments during the synthesis process on hydrogen production activity are relatively limited.

[0114] Figure 3 The stability diagram of hydrogen production of the composite nano-dot porous carbon nitride photocatalyst synthesized in Example 1 is shown in the following figure. Figure 2 Same. According to Figure 3 It can be seen that within the reaction time of 20 hours, the photocatalyst of the present invention has good photocatalytic hydrogen production stability and photocatalytic hydrogen production activity.

[0115] Figure 4 The histogram of visible light hydrogen production rate of composite nanodot porous carbon nitride photocatalysts synthesized in Examples 1 to 9, the test conditions are as follows: Figure 2 Same. According to Figure 4 It can be seen that the ratio of the loaded Ni nanodots and CoO nanodots in Example 1 is the optimal ratio for improving the photocatalytic hydrogen production performance.

[0116] Figure 5 The X-ray diffraction patterns of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown in FIG. Figure 5 It can be seen that the X-ray diffraction patterns of the porous carbon nitride synthesized in Example 1 and Comparative Examples 1, 2, and 3 are basically consistent, and all show diffraction peaks corresponding to the (002) plane and (100) plane of graphite phase carbon nitride, indicating that loading metal nanodots on the surface of the porous carbon nitride does not change the structure of the synthesized porous carbon nitride.

[0117] Figure 6The scanning electron microscope images of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Example 1. (a) is a scanning electron microscope image of the composite nanodot-loaded porous carbon nitride photocatalyst for photocatalytic hydrogen production synthesized in Example 1, and (b) is a scanning electron microscope image of the porous carbon nitride synthesized in Comparative Example 1. Figure 6 It can be observed that the porous carbon nitride is a two-dimensional layered structure, and the porous phase carbon nitride obtained by loading the composite nanodots of the present invention obviously has more wrinkles and holes, indicating that the loaded composite nanodots have a great modifying effect on the micromorphology of the graphite phase carbon nitride.

[0118] Figure 7 Transmission electron microscopy image of porous carbon nitride photocatalyst synthesized in 1, from Figure 7 It can be observed that there are obvious nanodots on the porous carbon nitride obtained by loading the composite nanodots according to the present invention, and the lattice fringes thereon are 0.246nm and 0.203nm corresponding to the (111) surface of CoO and the (111) surface of Ni, respectively, indicating that the CoO and Ni nanodots are successfully loaded on the porous carbon nitride surface.

[0119] Figure 8 The in-situ X-ray photoelectron spectrum of the porous carbon nitride photocatalyst synthesized in Example 1, wherein (a), (b), (c), and (d) are the C1s, N 1s, Ni 2p, and Co 2p spectra, respectively. It can be clearly observed from the figure that under light and dark conditions, the binding energy of the C1s and N1s peaks of the loaded composite nanodot porous carbon nitride photocatalyst obtained in Example 1 remains basically unchanged. On the contrary, under light conditions, the Ni 2p peak shifts significantly to a lower binding energy, while the Co 2p peak shows a significant positive shift. Generally, a decrease in binding energy indicates an increase in electron density, meaning that the corresponding atom acts as an electron acceptor. Conversely, an increase in binding energy indicates that the atom acts as a hole reservoir. In Ni1-PCN-CoO 0.5 In the experiment, a large number of photogenerated electrons accumulated on the nickel nanodots and were subsequently consumed in the hydrogen evolution reaction, indicating that the nickel nanodots acted as electron acceptors and provided active sites for the reaction. Meanwhile, photogenerated holes accumulated around the cobalt oxide nanodots, which acted as hole reservoirs. This suggests that the coexistence of the two nanodots on the surface of the synthesized composite nanodot-loaded porous carbon nitride photocatalyst for photocatalytic hydrogen production promoted the effective separation of photogenerated electrons and holes on the PCN surface, significantly enhancing its hydrogen evolution activity.

[0120] Figure 9The UV-visible absorption spectra of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown. It can be clearly observed from the figure that the UV-visible absorption spectra of the graphite-phase carbon nitride synthesized in Comparative Examples 1 and 2 almost overlap, indicating that the introduction of CoO nanodots has no effect on the light absorption of carbon nitride. However, the light absorption of the UV-visible absorption spectrum corresponding to the catalyst synthesized in Comparative Example 3 shows a significant blue shift. At the same time, the light absorption of the composite nanodot-loaded porous carbon nitride photocatalyst synthesized in Example 1 further blue shifts, indicating that light absorption is not the main reason for the improved photocatalytic hydrogen production performance.

[0121] Figure 10 The electron paramagnetic resonance spectra of the porous carbon nitride photocatalyst synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown in FIG. Figure 10 It can be seen that the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 all have a characteristic single Lorentz line and the same g value (2.003), which is caused by the delocalized electrons in the carbon atoms of the π conjugated aromatic ring. And the composite nanodot-loaded porous carbon nitride photocatalyst obtained by loading two nanodots in Example 1 of the present invention exhibits a significantly stronger spin characteristic peak than the graphite phase carbon nitride synthesized in Comparative Examples 1, 2, and 3, indicating that the simultaneous loading of Ni and CoO nanodots on the porous carbon nitride introduces a large number of unsaturated sites, thereby accelerating the delocalization of π-series electrons, increasing the electron density, and being more conducive to the photocatalytic hydrogen production reaction. In addition, under light conditions, the EPR signal of the porous carbon nitride photocatalyst synthesized in Example 1 and Comparative Examples 2 and 3 is greater than the enhancement degree of the porous carbon nitride photocatalyst synthesized in Comparative Example 1 under dark conditions, indicating that the introduction of nanodots promotes light excitation and carrier transport.

[0122] Figure 11 The steady-state fluorescence spectra of the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 are shown. As can be seen from the figure, the porous carbon nitride photocatalysts synthesized in Example 1 and Comparative Examples 1, 2, and 3 all have similar characteristic peaks, and the stronger characteristic peaks of the porous carbon nitride photocatalyst obtained in Comparative Example 1 indicate that the internal photogenerated carriers are seriously recombinated. The characteristic peak intensities of the composite nanodot porous carbon nitride photocatalysts loaded with Ni and CoO nanodots on the surface of the porous carbon nitride of the present invention are significantly weakened, and the further reduction in the characteristic peak intensity of the composite nanodot porous carbon nitride photocatalyst loaded with two nanodots in Example 1 indicates that the loading of Ni and CoO nanodots can effectively suppress the recombination of photogenerated carriers and promote their separation. When the two are simultaneously loaded on the surface of the porous carbon nitride, the synergistic effect between the two can further enhance the suppression of photogenerated carrier recombination, thereby significantly improving the photocatalytic hydrogen production performance.

[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the invention shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a composite nanodot-loaded porous carbon nitride photocatalyst, characterized in that: The following steps are involved: Step 1, weighing melamine, cyanuric acid and thiocyanic acid in a mass ratio of (1.3-1.36):1.26:1; Step 2: At room temperature, the melamine and cyanuric acid weighed in step 1 are added successively to 100-140 mL of deionized water, and stirred to obtain a mixed solution of melamine and cyanuric acid; the weighed thiocyanuric acid is added to 100-140 mL of deionized water to dissolve to obtain a thiocyanuric acid solution; Step 3, adding the mixed solution of melamine and cyanuric acid obtained in step 2 dropwise to the thiocyanuric acid solution, stirring for 9-11 hours, filtering and drying to obtain a solid supramolecular polymer, placing the obtained solid supramolecular polymer in a vacuum oven at 50-70° C. and drying for 9-11 hours, grinding into powder to obtain a carbon nitride precursor; Step 4: The carbon nitride precursor obtained in step 3 is heated at 2-4 ° C min in N2 atmosphere. -1 The heating rate is increased to 550-650°C and maintained for 1-3 hours, and then the temperature is naturally lowered to obtain porous carbon nitride; Step 5: Dissolve the porous carbon nitride obtained in step 4 in anhydrous ethanol, ultrasonicate for 10-15 min, then add the CoCl2 ethanol solution dropwise to the solution and stir for 4-6 h, then perform rotary evaporation to obtain powder, and heat the powder at 2.5-3.5 ° C min -1 The heating rate was increased to 180-220° C. and kept at this temperature for 1.5-2.5 hours, and then naturally cooled to obtain a porous carbon nitride photocatalyst loaded with CoO nanodots; Step 6: dissolve the CoO nanodot-loaded porous carbon nitride photocatalyst obtained in step 5 in anhydrous ethanol, ultrasonicate for 10-15 min, add Ni(NO3)2 anhydrous ethanol solution dropwise, stir for 4-6 h, and then rotary evaporate again to obtain powder; the obtained powder is heated at 2.5-3.5℃min in an Ar-H2 atmosphere. -1 The heating rate is increased to 180-220° C. and kept warm for 1.5-2.5 hours to obtain a loaded composite nano-dot porous carbon nitride photocatalyst for photocatalytic hydrogen production.

2. The method for preparing the composite nanodot-loaded porous carbon nitride photocatalyst according to claim 1, characterized in that: In step 4, the temperature is raised by calcination, and N2 gas is first introduced before calcination, and the temperature is maintained at room temperature for 20-40 minutes.

3. The method for preparing the composite nanodot-loaded porous carbon nitride photocatalyst according to claim 1, characterized in that: In step 5, 60-100 mg of the porous carbon nitride obtained in step 4 is dissolved in 40-60 mL of anhydrous ethanol.

4. The method for preparing the composite nanodot-loaded porous carbon nitride photocatalyst according to claim 1, characterized in that: Add CoCl2 ethanol solution in step 5 2+ The mass ratio of the porous carbon nitride is 0.25-1 wt %.

5. The method for preparing the composite nanodot-loaded porous carbon nitride photocatalyst according to claim 1, characterized in that: In step 6, the obtained CoO nanodot-loaded porous carbon nitride photocatalyst is dissolved in 40-60 mL of anhydrous ethanol.

6. The method for preparing the composite nanodot-loaded porous carbon nitride photocatalyst according to claim 1, characterized in that: Add Ni(NO3)2 anhydrous ethanol solution as described in step 6, Ni 2+ The mass ratio of the porous carbon nitride photocatalyst to the cobalt oxide nanodots is 0.5-1.5 wt %.

7. A composite nanodot-loaded porous carbon nitride photocatalyst prepared according to the method of any one of claims 1 to 6.

8. A composite nanodot-loaded porous carbon nitride photocatalyst prepared according to the method of any one of claims 1 to 6, used in photocatalytic hydrogen production.

Citation Information

Cited By

  • Preparation method of cobalt oxide-based composite material for 3-octanone detection

    CN121656339A

  • Carbon nitride-Pt-sulfur cobalt zinc photocatalytic hydrogen production material as well as preparation method and application thereof

    CN122032611A